Health system transformation to support global health security / Nik Raihan Afiq Nik Mohd Asri and Assoc. Prof. Dr. Mahmathi Karuppannan - Nik Mohd Asri, Nik Raihan Afiq; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
From 1st March to 24th May of 2023, Universitas Dutabangsa, Indonesia organized an international program called the 3rd ICOHEX 2023 International Competition on Health And Student Exchange with the theme "Health System Transformation to Support Global Health Security". The program includes activities such as webinars centered on stunting among children, talent competitions for song cover, dance, and oral speech, and other competitions like designing poster, writing essays, creating creative and learning videos . All of the activities were conducted online. UiTM participated in the event as a co-host and Dr Fazleen Hatta from Department of Pharmacology and Pharmaceutical Chemistry delivered a talk entitled "Strengthening health resilience through drug and vaccine research".